Bibliometric Analysis The Effect of Health Protocol Social Marketing Communications on New Adaptations Covid-19 Pandemic - Moch Bima Syaputra Winardi; Muhammad Chabibur Rohman; M Yusach Ryadh Rasyid; Andre Astana Putra; Ferry Adhi Dharma (Universitas Muhammadiyah Sidoarjo, 2022)
The bibliometric approach is an analysis carried out with the aim of developing scientific fields taken from the analysis of previous journals or articles selected through the Web of Science, Scopus, Google Scholar and Semantic Scholar. The purpose of using bibliometric analysis is to find out how many journals with the theme of the influence of social marketing communication on health protocols on new adaptations during the covid-19 pandemic. The purpose of this study is to measure the depth of public awareness regarding the application of health protocols during the COVID-19 pandemic. With the elements contained in social marketing communication theory, it can increase knowledge and change people's behavior regarding the application of health protocols during the covid-19 period. The method for measuring the quantity of publications is done by taking data from Google Scholar and Semantic Scholar then analyzed using Vos viewer. The results of the visualization will be explained in detail through theoretical dialogue and the results of bibliometric analysis from journal publications with keywords Bibliometrics, Social marketing communication, Health protocols, Covid-19 can be additional references and research can be developed more broadly.